Travel Angle Control of Quanser Bench-top Helicopter based on Quantitative Feedback Theory Technique - A. H. Mohd Hairon; H. Mansor; T. S. Gunawan; S. Khan (Institute of Advanced Engineering and Science, 2016)
A three degree of freedom (3-DOF) bench-top helicopter is a simplified aerial vehicle which is used to study the behaviors of the helicopter as well as testing multiple flight control approaches for their efficiency. Designing helicopter’s dynamic control is a challenging task due to the presence of high uncertainties and non-linear behavior. The main objective of this research is to achieve robust control over the helicopter model regardless parameter variation and disturbances using robust control technique, Quantitative Feedback Theory (QFT). QFT utilizes frequency domain methodology which ensures plant’s stability by considering the feedback of the system and thus removing the effect of disturbances and reducing sensitivity of parameter’s variation. The proposed technique is tested against LQR-tuned PID controller in both simulation and real hardware environment to verify its performance. The results obtained shown us that QFT algorithm managed to reduce settling time and steady state error of about 80% and 33% respectively over the classical PID controller.